Effectiveness of hospital-to-home transitional care interventions and consultation for implementation in Sudan: a scoping review of systematic reviews - Mohamedsharif, Asma; Elfeaki, Mohammed; Bushra, Rayan; Gemperli, Armin (Frontiers in Health Services, 2023)
Background: Hospital discharge is often associated with a lack of continuity resulting in fragmented care, particularly in low-income countries. As there is limited information about interventions in these countries and no study evaluating the effectiveness of hospital discharge interventions, we conducted a scoping review to identify effective hospital-to-home transitional care interventions and explore their applicability in a low-income country (Sudan). Methods: Our scoping review of systematic reviews and meta-analyses classed interventions as effective, ineffective, undesirable, or uncertain, based on the quality of their evidence and their estimated effects on the following outcomes: readmission rates, mortality, costs, quality of life, and adverse outcomes) and certainty of evidence. Our authors from Sudan used the SUPPORT summary tool to determine if three effective interventions could be implemented in Sudan. Results: Out of 3,276 articles that were identified, and 72 articles were reviewed, 10 articles has been included in the review. Seven interventions were classified as effective, one as ineffective, and none with undesirable effects. Eight interventions were classified as having an uncertain effect. The effective interventions were composed of home visits, information and communication technology (ICT), case manager models, multidisciplinary teams, and self-management support. Conclusions: The finding of this study suggested that a combining two to four interventions can improve enhance hospital-to-home transitional care. Effective interventions are composed of home visits, ICT, case manager models, multidisciplinary teams, and self-management support. The implementation of these interventions in Sudan was found to be undermined by contextual factors such as inadequate human resources, telecommunication instability, and inequality in accessibility. These interventions could be tailored based on an in-depth understanding of the contextual factors in low-income countries that influence implementation.